Programa Fome Zero: assistencialismo ou desenvolvimento? - Xavier, Bruno Damasceno (2020)
The objective of this dissertation was to describe and analyze the process of implementing the Zero Hunger Program (2003). For this, we started from the hypothesis of programmatic differences between the proposals contained in the Zero Hunger Project (2001) and the actions and policies implemented by the Program during the first term of the Lula Government. One of the Project's great differentials is the incorporation of the concept of Food and Nutritional Security (SAN) as a guide for public policies. After analyzing the evolution of this concept and its adoption in Brazil, the actions carried out by the ministries and secretariats responsible for the Program (MESA, MDS and SESAN) were described. Then, the matrices of thought and ideological conflicts internal to the Federal Government at the time were pointed out and evaluated. For this, the methodology used consists of the theoretical-historical method of analysis, performing a critical reading of public documents, books on SAN, texts containing interviews of experts in SAN who actively participated in the discussions on the implementation of the Program, and also writings of politicians members of theWorkers' Party. In addition to the analysis of the data made available by SESAN on the actions developed between 2004 and 2006. From these analyzes, it is concluded that some changes occurred in the way of how to implement the program and fight hunger and poverty in the country, changing some conceptions and paradigms of the original proposals. These changes made the Program more focused on specific population groups, reducing some of the development potential of the 2001 Project. The reasons for these changes, to a large extent, are to be found in the political and ideological disputes internal to the Workers' Party, and also external, in the party alliances made by the Federal Government, represented in the different ministries.